Analisis Efektivitas Pengelolaan SDM dalam Upaya Peningkatan Produktivitas Kerja pada PDAM Tirta Bhagasasi Cabang Tambun Kabupaten Bekasi Tahun 2022 - Fikri Firdaus; Diana Prihadini; Siti Nurbaity (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
Basically, human resources are resources that are needed by an organization. Because, human resources are resources that play an active role in the course of an organization and the decision-making process. The right man on the right place, will lead an organization to maximum performance results and reduce errors in tasks or work. The purpose of this study was to determine and analyze the effectiveness of HR management at PDAM Tirta Bhagasasi Tambun Branch, Bekasi Regency. The method used is a qualitative approach with a descriptive type of research. The results of this study based on the analysis carried out productivity have been good, where in the adequacy indicator efforts have been made with training, employee efficiency is still not good with performance and facilities that are still not good but reward mechanisms have been implemented to improve performance, in the infikator accuracy is still not good, where the level of employee discipline towards compliance that is still lacking for responsiveness is good, Various trainings and bimtek have been carried out to improve employee responsiveness, the level of similarity is quite good because the training has been adjusted to the needs in the field. The obstacles that occur in PDAM Tirta Bhagasasi Tambun Branch, Bekasi Regency are employee indiscipline and non-compliance with the rules that have been set at PDAM Tirta Bhagasasi Tambun Branch, Bekasi Regency and the placement of employees at the time of recruitment is not based on the educational background or skills possessed by the employee. The efforts made by PDAM Tirta Bhagasasi Tambun Branch, Bekasi Regency are to Provide training in accordance with the employee's job desk in an effort to improve skills in addition to employee disciplinary efforts with the My Bhagasasi application for attendance.